Case report: Primary hemophagocytic syndrome triggered by dengue infection. (2021) - Devi, Kanta; Ali, Natasha
Abstract: HLH is a progressive syndrome of unchecked immune activation and tissue damage. If left untreated, patients with HLH survive for only a few months, due to progressive multi-organ failure. Prompt initiation of treatment for HLH is essential for the survival of affected patients. Several conditions are responsible for triggering HLH in clinically stable patients who respond to treatment of the underlying condition alone. These conditions include infection, rheumatological diseases and lymphoid malignancies. We report a rare case of primary HLH in a 32-year-old female who presented with fever, abdominal pain, pancytopenia and splenomegaly with the triggering factor being Dengue infection.